Algebraic Analysis of Branching Processes - DELFIEU, DAVID; Comlan, Maurice; SOGBOHOSSOU, MEDESU (My University, 2014)
Combinatory explosion is a limit which can be en- countered when a state space exploration is driven on large specification modeled with Petri nets. Technics like unfolding have been proposed to cope with this problem. This paper presents an axiomatic model to reduce unfoldings to canonic forms which preserves conflicts.
Keywords: Petri Nets; Unfolding; Branching process; Algebra